Synthesis and characterization of meso-substituted porphyrin - Muhammad, Muhammad Tahir (2014)
Porphyrins and their analogs are a class of chemically and biologically important compounds that have found a variety of applications in different fields such as catalysis and medicine, especially for photodynamic cancer therapy (PDT). The physical, chemical, and biological dependence of the peripheral substituents of porphyrins on their properties has prompted great effort towards the synthesis of new porphyrins with different electronic, steric, and conformational environments. Significant improvement has been made to develop various synthetic methodologies in preparing the functionalised porphyrins. However, the challenges still remain especially to prepare asymmetrical type of porphyrin system which is useful for numerous applications. In this study, we have utilised three synthetic methods; condensation, bromination and Suzuki Cross Coupling reactions to synthesis porphyrins with different meso-substituents; A2-, AB-, A2B-, as well as ABC- type porphyrins. The synthetic strategy is developed based on dipyrromethane as the main precursor to prepare di-substituted porphyrin via Lindsey method, and followed by bromination reaction to obtain tri-substituted porphyrin. Eventually, the reaction was prolonged by using Suzuki- Cross coupling reaction to attain tri-substituted porphyrin. All of the compounds were characterized using Proton Nuclear Magnetic Resonance (1H-NMR), Carbon Magic Angle Spin Nuclear Magnetic Resonance (13C-NMR), ultraviolet (UV) and infrared (IR) spectroscopies.